Estimation of Highway Maintenance Cost due to Heavy Truck Traffic - เย็นฉ่ำ, ภาณุพงศ์; แสงเพชรงาม, บุญชัย (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
This article aims to study a predictive model of pavement damage that is suitable for highways in Thailand. The damage results are sufficient to account for long-term maintenance costs. and analyze the cost of damage to cover the cost of maintenance of the road structure caused by heavy trucks in the future The study modeled the paved road structure using the HDM-4 program using the data of Highway 344 Rayong-Ban Bueng. which is located not far from the truck weighing station in the modeling The model is 1 km long and has 4 traffic lanes. The test was performed by using models of all 4 types namely, medium trucks, heavy trucks, semi-trailers and trailers. The damage caused by heavy trucks for 20 years was simulated, namely cracking, ravelling, potholing and rutting. The relationship between structural strength, truck volume and road section It tends to indicate future damage. Therefore, the maintenance model used in the HDM-4 program was considered to estimate the cost of pavement maintenance and quality control over a 20-year period appropriate to the highway.